1988
DOI: 10.2307/3282213
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Action of the Anticoccidial Diclazuril (Clinacox[registered]) on the Developmental Stages of Eimeria tenella: An Ultrastructural Evaluation

Abstract: A single 5-mg/kg oral dose of diclazuril affected both the asexual and sexual development of Eimeria tenella in experimentally inoculated chickens. In second-generation schizonts, early growth and nuclear divisions progressed normally, but a marked inhibition of merozoite formation was observed. Exogenesis of merozoites was largely prevented, whereas production of micronemes, amylopectin granules, and dense bodies and the formation of rhoptries, conoid, and pellicle continued. All these subcellular organelles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…Similar phenomenon has been observed in other studies (Verheyen et al 1988(Verheyen et al , 1989McDougald and Galloway 1977;Taylor et al 2003). It may be that vacuolation and degeneration is a common phenotype in parasites after drug treatment.…”
Section: Discussionsupporting
confidence: 73%
“…Similar phenomenon has been observed in other studies (Verheyen et al 1988(Verheyen et al , 1989McDougald and Galloway 1977;Taylor et al 2003). It may be that vacuolation and degeneration is a common phenotype in parasites after drug treatment.…”
Section: Discussionsupporting
confidence: 73%
“…Diclazuril is a nucleoside analogue thought to be involved in nucleic acid synthesis, possibly affecting later phases of coccidia differentiation (Verheyen et al 1988). It has been shown to affect parasite wall synthesis resulting in the formation of an abnormally thickened, incomplete oocyst wall and zygote necrosis in both E. brunetti and E. maxima (Verheyen et al 1989).…”
Section: Products With Unknown Mode Of Actionmentioning
confidence: 99%
“…Studies have demonstrated that this compound has a broad spectrum activity against all pathogenic Eimeria species in chickens. In E. tenella, detailed histological, clinical, and ultrastructural studies have shown that diclazuril, given in a single oral dose at different periods after inoculation, was fully effective against asexual as well as sexual stages Verheyen et al 1988). It was found that treatment with diclazuril downregulated mz-ADF mRNA expression by 63.86% in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Diclazuril, a benzeneacetonitrile anticoccidial, has potent activity against the asexual and sexual stages of E. tenella development (Xie et al 1991;Maes et al 1988;Verheyen et al 1988;Nodeh et al 2008). However, the exact mechanisms that drive inhibition of diclazuril in second-generation merozoite remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%